Different opportunities to influence the visual "attention window" - Hüttermann, S.; Memmert, D. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Visual attention is essential in many areas and situations ranging from everyday life to the workplace. People have to allocate their visual attention from a focused target to a wide scope and vice versa in fractions of a second. Other events require the conscious perception of two objects or scenes at the same time. Many situations including traffic or sports suggest that the focus of attention has a limited size and can be influenced by various factors. We introduced the attention window task, a new measurement of attention breadth, in which people must observe two equally attention-demanding stimuli at the same time in order to respond correctly. Our findings indicate that differences in the spatial distribution of attention result from, for example, effects of age or experiences as well as emotional processes and those affected by current motivation. The maximum spatial extent of attention is ellipsoidal with greater breadth along the horizontal axis than the vertical one. In contrast to the visual field, the elliptical shape of the attention window does not alter by a change of the head position but constantly maintains its oval shape parallel to the ground. We discuss the application of different strategies and factors to improve and adjust performances in different everyday occurrences requiring the ability to pay attention to two peripheral objects at the same time.